Biochemical and structural analysis of shelterin subcomplexes - Inian, Oviya (2018)
Telomeric chromatin consists of tandem ‘TTAGGG’ DNA repeats that associate with a telomere-specific complex, known as shelterin. Shelterin has an indispensable role in telomere length homeostasis and protection against genomic instability arising from erroneous DNA damage responses. Shelterin collectively consists of six proteins - Telomeric repeat binding factors 1, 2(TRF1 and TRF2), Protector of telomeres 1 (POT1), TRF1 interacting nuclear factor 1(TIN2), TIN2 POT1 interacting protein (TPP1) and Repressor/activator protein 1(RAP1). Specific mutations in shelterin proteins leading to telomere dysfunction have been reported in human diseases such as Dyskeratosis, Hoyeraal-Hreidarsson syndrome and cancer. Although structures of the domains of the individual proteins are well-studied, the intact shelterin complex and its subcomplexes remain largely uncharacterized. Results presented in this thesis discuss the biochemical purification of the shelterin subcomplexes TRF2-RAP1-TIN2S and the telomerase recruitment complex POT1-TPP1-TIN2S. The subcomplexes are further characterized by analysis of the stoichiometry and interaction with DNA. Structures of TRF2-RAP1-TIN2S and POT1-TPP1-TIN2S obtained through negative stain electron microscopy (EM) are presented. Cryo-EM imaging of DNA and nucleosome core particle (NCP) samples utilizing Volta phase plate is shown. Subsequent Volta phase plate imaging of POT1-TPP1-TIN2S is presented, showing promise for forthcoming structure determination using cryo-EM. Finally, approaches to obtain high-resolution structures of shelterin subcomplexes in the future are discussed.